Efeito da carga hidráulica na uniformidade da irrigação e fertirrigação em sistema de gotejamento - Tessaro, Evandro (2012)
The irrigation tracked by gravity is a technique applied by the family farming that has been spread in Brazil and is used in social programs of some States or directly traded to producers. Irrigation systems have simplified management and let it cheaper. They intensify agricultural yield, increase the prospects of life in the countryside and, therefore, settle the small producers down in their properties. There has been a long time that fertirrigation is being used, but it has several types. The statistical control of quality is a tool used to evaluate the quality of a product and present their negative changes in order to get information that improves the quality of such product. Thus, this trial aims at studying the effect of hydraulic load on the uniformity of water and fertilizer application using dripping system. The experiment was carried out in the prototyping Laboratory at Western Paraná State University. A dripping irrigation system was evaluated to be applied in family farming. There were three pressures (1.0; 1.5 and 2.0 mca) and a completely randomized design was used according to ABNT regulations (NBR ISO 9261) for runoff collection proposed by Keller & Karmeli (1975). The treatments were organized to be compared so that data were statistically processed. In addition, the irrigation system was also classified according to the ASABE regulations. The statistical control of system quality was also performed to analyze its quality. The coefficients of each treatment achieved the excellent level according to their ratings. Shawhart control charts showed significant effect for the examined factors. The system has obtained an excellent process capability according to the analyses of uniformity. There also was a significant relationship among coefficients (CUC, CUD and CV) with the capability of flow data process